CHARACTERISTICS OF FASHION BLOGS IN DIFFERENT LINGUACULTURES (Journal of Science-Innovative Research in Uzbekistan, 2024)
The article aims to challenge the traditional view of fashion blogs as a genre, instead proposing that they should be considered as a type of institutional discourse. The study analyzed the top 10 fashion blogs from four languages (English, Spanish, Russian, and French) using various research methods, including classification, synthesis, and analysis, to support this new perspective.